Evaluation of jaw function, oral health-related quality of life, and nutritional status during oral rehabilitation procedures – a pilot study - Tina Thakrar; Abhishek Kumar; Catharina Göthberg; Anastasios Grigoriadis (Acta Odontologica Scandinavica)
Aims: To evaluate limitations in jaw function, oral health-related quality of life (OHRQoL), and nutritional status during extensive oral rehabilitation procedures.